Targeting TGFβR2‐mutant tumors exposes vulnerabilities to stromal TGFβ blockade in pancreatic cancer. Issue 11 (14th October 2019) - Huang, Huocong; Zhang, Yuqing; Gallegos, Valerie; Sorrelle, Noah; Zaid, Mohamed Medhat; Toombs, Jason; Du, Wenting; Wright, Steven; Hagopian, Moriah; Wang, Zhaoning; Hosein, Abdel Nasser; Sathe, Adwait Amod; et al.
Abstract: TGFβ is important during pancreatic ductal adenocarcinoma (PDA) progression. Canonical TGFβ signaling suppresses epithelial pancreatic cancer cell proliferation; as a result, inhibiting TGFβ has not been successful in PDA. In contrast, we demonstrate that inhibition of stromal TGFβR2 reduces IL‐6 production from cancer‐associated fibroblasts, resulting in a reduction of STAT3 activation in tumor cells and reversion of the immunosuppressive landscape. Up to 7% of human PDA have tumor cell‐specific deficiency in canonical TGFβ signaling via loss of TGFβR2. We demonstrate that in PDA that harbors epithelial loss of TGFβR2, inhibition of TGFβ signaling is selective for stromal cells and results in a therapeutic benefit. Our study highlights the potential benefit of TGFβ blockade in PDA and the importance of stratifying PDA patients who might benefit from such therapy. Synopsis: Canonical TGFβ signaling suppresses epithelial pancreatic cancer (PDA) cell proliferation; as a result inhibiting TGFβ has not been successful in pancreatic cancer. In TGFβR2‐mutant tumors, inhibition of TGFβ signaling in stromal cells results in a therapeutic benefit. TGFβ induces fibroblasts to produce IL‐6 that promotes tumorigenesis via STAT3 activation in PDA cells. TGFβR2 blockade inhibits STAT3 activation in PDA cells and alters the immune microenvironment. TGFβR2 blockade has therapeutic efficacy in PDA that harbors loss‐of‐function mutations in Tgfbr2 but not in tumors that have intact TGFβ signaling. Efficacy of TGFβR2 blockade in TGFβR2‐mutant tumors is due to the inhibition of the TGFβ signaling in stromal cells and IL‐6 signaling in cancer cells and NK cells. Abstract : Canonical TGFβ signaling suppresses epithelial pancreatic cancer (PDA) cell proliferation; as a result inhibiting TGFβ has not been successful in pancreatic cancer. In TGFβR2‐mutant tumors, inhibition of TGFβ signaling in stromal cells results in a therapeutic benefit.